Patch testing in New Zealand: Barriers to evidence‐based care. (10th September 2020) - Sapsford, Sabrina; Cheng, Harriet; Judd, Lissa
Abstract: Allergic contact dermatitis is a disabling condition, significantly impacting on quality of life, which can only be alleviated by identification and avoidance of a relevant allergen. Patch testing remains the gold standard diagnostic test for allergic contact dermatitis. The consistency with which patch testing is used varies throughout the world. The purpose of this study was to look at the adequacy of current patch testing practice in New Zealand. We undertook literature review of current guidance regarding patch testing and created a web‐based survey to evaluate use of patch testing in New Zealand. This was sent to all 75 vocationally registered New Zealand dermatologists. Of respondents, 46% do not perform patch testing. The most commonly cited barriers were lack of nursing support, poor remuneration, time pressure and lack of facilities. 23% noted that public patch testing services are not available in their region. The majority do not record patch test results in a database. Access to and utilisation of patch testing in New Zealand is suboptimal. Increasing services in the public sector requires investment by health boards, as there remains a dermatology workforce shortage in New Zealand. In private practice, patients often find it unsatisfactory to pay for negative tests, and adequate remuneration of patch testing by private insurers is necessary. Surveillance of patch test results at a national level is lacking, and the development of a centralised database to identify common allergens affecting our population is recommended.